Improving project success rate in indonesia through applied project management and good practice - Irawadi, Delano; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2016)
Abstract - Research conducted in this thesis is an attempt to identify perception and perceived project state from professionals and practitioners which involved projects in various industrial sectors about how they see the condition of projects in Indonesia. Criteria which used were successful project which have the characteristics according to schedule, in accordance with budgeted costs, and according to user needs. This research starts with an analysis of the relevant literature, this study identified 14 factors that cause projects to fail. For labor strike factor not considered in this study because of demographic industry in this study (IT, Telecommunications, Technology, Energy, Oil & Gas, and Construction) not represent that this factor was happen frequently. Information is obtained through the survey instrument, data were collected from 81 respondents which is then analyzed and matched with solutions applied good practices, tools & technique related to project management disciplines. Amongst the highlights of the findings is that there is a gap between the skills and knowledge taught on campus, university and professional institutions with what is practiced in the workplace. This shows the need for the application of methodology project-based learning which involves a real project environment with real-world problems so that learner can understand how to apply tools & technique in practical ways. Other finding is the need to manage the "lessons learned" so that learner does not repeat the same mistakes, learn from what happened to the previous project.Â Key Word: Project Management, Additive Weighting Technique, Target Contract